Risk of HBV reactivation in HBV/HCV-co-infected HCV-treated patients: A single-center study - Young Joo Park; Ki Youn Yi; Hyun Young Woo; Jeong Heo; Geun Am Song (PLoS ONE, 2025)
Hepatitis B virus (HBV) reactivation in patients with HBV/hepatitis C virus (HCV) co-infection due to direct-acting antiviral agent (DAA) therapy is a growing concern. This study focused on 47 patients with chronic hepatitis C (CHC) and positivity for HBV surface antigen (HBsAg) who were treated with interferon (IFN)-based therapy, DAA, or DAA after IFN-based therapy failure and followed for a median of 53 months. Here, we aimed to determine HBV reactivation rates and associated factors, the incidence of HBV and liver-related events, and the rate of sustained virologic response (SVR) for HCV. Fifteen (15/47, 31.9%) patients experienced HBV reactivation during or after HCV treatment. This reactivation occurred significantly more frequently in patients who received DAA treatment after IFN-based treatment failure than in those who received IFN-based treatment (IFN-based vs. DAA vs. DAA treatment after IFN-based treatment failure 11.8% vs. 35.3% vs. 53.8%, respectively; p = 0.046). The interval from HCV treatment initiation to HBV reactivation was shortest in the DAA group (4.2 months), followed by the DAA after IFN-based treatment failure group (6.4 months) and the IFN-based treatment group (44.5 months) (p < 0.001). One case of HBV-related hepatitis spontaneously resolved after 4 weeks. The rate of SVR for the entire cohort was 87.2%, with no significant difference in this regard among the IFN-based treated, DAA-treated, and DAA-treated after IFN-based treatment failure arms at 82.4%, 88.2%, and 92.3%, respectively. HBV reactivation in HBsAg-positive CHC patients is more common and occurs earlier in those who receive DAA treatment after IFN-based treatment failure than in those with IFN-based treatment. Therefore, all patients with CHC should be tested for HBV exposure prior to DAA treatment. In addition, HBsAg positive patients, especially those among whom have previously experienced IFN-based treatment failure, should be closely monitored for HBV reactivation during DAA therapy.